Mouvement et pulsion. Note sur Bernet lecteur de Heidegger lecteur d’Aristote - Camilleri, Sylvain (Bollettino Filosofico, 2020)
In this paper, I would like to elaborate on the part of Heidegger’s hermeneutics of facticity that is devoted to the works of Aristotle, especially his Physics. More specifically, my aim is to shed light upon an “hermeneutic” reading of this part of the hermeneutics of facticity by showing how the great Husserl scholar Rudolf Bernet, in an important monograph published in 2013, draws upon Heidegger’s reading of Aristotle in order to address issues seemingly of his own. I will discuss the questions raised by the articulation of drive (“pulsion”) and movement in Bernet’s study out of a phenomenological interpretation of Aristotle’s kinesis as developed by Heidegger in the early 1920’s and beyond. I will further lay out some new questions regarding the historical as well as systematic relationships between Heidegger’s et Bernet’s respective projects. Keywords: Aristotle, Bernet, Drive, Facticity, Hermeneutics, Movement